Characterization and functional properties of gelatin extracted from goatskin - , Zilhadia; H, Yahdiana; Jaswir, Irwandi (Universiti Putra Malaysia, 2018)
Gelatin from goatskin pretreated with hydrochloric acid and extracted with distilled water at 60o C for 9 hours was characterized and compared to that of bovine skin gelatin (BSG). A yield of 10.26% (wet weight basis) was obtained. Goatskin gelatin (GSG) had high protein (86.58%), suitable moisture (9.58%), low fat (1.46%) and low ash (0.11%) content. The functional properties of GSG including gel strength (301 g bloom) and emulsion activity index (94.27%) were higher than the functional properties of BSG including gel strength (192 g bloom) and emulsion activity index (49.74%). The foaming property of GSG (102%) was lower than that of BSG (164.67%). This study shows that GSG has a high potential for application as a source of commercial gelatin.